Analytical applications of ionic liquids - Koel, Mihkel (London : World Scientific Publishing Europe Ltd., 2017)
'Analytical Applications of Ionic Liquids reviews the current research in analytic chemistry, covering subjects as diverse as separation science, chromatography, spectroscopy and analytical electrochemistry. As scientific developments have moved into the 21st century, they have increasingly had to take into account the effects on the environment, both locally and globally. Because of this, the search for applications of ionic liquids is growing in every area of analytical chemistry. Here, material is presented by specialists, giving a critical overview of the current literature surrounding this increasingly prominent topic. Analysis is carried out on latest achievements and applications, followed by critical discussion of possible future developments. As well as stimulating further research among established analytical chemists, this book can also be used for undergraduate and graduate courses on chemistry and chemical technology.'--Publisher's website.
Title from PDF file title page (viewed October 10, 2016).
Includes bibliographical references and index.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Ionic solutions; Ionic structure; Chemistry, Analytic; Electronic books